Systematic elucidation of the bioactive alkaloids and potential mechanism from Sophora flavescens for the treatment of eczema via network pharmacology. (30th January 2023) - Lin, Yan; Chen, Xing-Jun; He, Lei; Yan, Xue-Long; Li, Qi-Rui; Zhang, Xu; He, Ming-Hui; Chang, Shuai; Tu, Bo; Long, Qing-De; Zeng, Zhu
Abstract: Ethnopharmacology relevance: Sophora flavescens is a frequently used traditional Chinese medicine (TCM) for the treatment of skin disorders, diarrhea, vaginal itching and inflammatory diseases. In particular, the root of S. flavescens combination with other herbs mainly treat eczema ailment in the clinical applications. However, a holistic network pharmacology approach to understanding the mechanism by which alkaloids in S. flavescens treat eczema has not been pursued. Aim of the study: To examine the network pharmacological potential effect of S. flavescens on eczema, we studied the alkaloids, performed protein targets prediction and investigated interacting signal pathways. Furthermore, animal experiment was carried out to evaluate its efficacy and real-time quantitative polymerase chain reactions (RT-qPCR) analysis was explored the mechanism of action. Materials and methods: The detail information on alkaloids from S. flavescens were obtained from a handful of public databases on the basis of oral bioavailability (OB ≥ 30%) and drug-likeness (DL ≥ 0.18). Then, correlations between compounds and protein targets were linked using the STRING database, and targets associated with eczema were gathered by the GeneCards database. Human genes were identified and subjected to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and Gene Ontology (GO) functional enrichment analysis. Particularly, matrine, the crucial alkaloid from S. flavescens, was estimated using a 2, 4-dinitrochlorobenzene (DNCB)-induced eczema Kunming (KM) mice model, administered (50 mg/kg and 10 mg/kg) to mice for 22 days. On the last day, the activities of serum tumor necrosis factor α (TNF-α), interleukin-4 (IL-4) and histopathologic examinations were determined. For further to elucidate the mechanisms, the mRNA levels of TNF-α, STAT3, TP53, AKT1, IL-6, JUN and EGFR in dorsal skin tissues were also tested. Results: Network analysis collected and identified 35 alkaloids from S. flavescens . Among them, in total 10 dominating alkaloids, including matrine, oxymatrine, sophoridine, sophocarpine, oxysophocarpine, allomatrine, sophoramine, anagyrine, cytisine and N-methylcytisine. And 71 related targets were provided of alkaloids for the treatment of eczema from S. flavescens . Furthermore, matrine dose-dependently (50 or 10 mg/kg, 22 days, apply to dorsal skin) remarkable decreased the serum levels of TNF-α and IL-4, and significantly alleviated the skin lesions. The effects of 50 mg/kg of matrine were almost identical to those of 200 mg/kg of the positive drug dexamethasone (DXM). The further RT-qPCR analyses could reveal that matrine down-regulate TNF-α, STAT3 and TP53 at transcriptional level in dorsal skin tissues. Conclusion: Pharmacological network analysis can utilize to illuminate the pharmacodynamic substances and the potential molecular mechanism of S. flavescens for treating eczema. Matrine, as the crucial alkaloid from S. flavescens, could be a promising drug candidate for the treatment of eczema ailment. Graphical abstract: Image 1 Highlights: 10 positive alkaloids and 71 protein targets from S. flavescens associated with eczema disorder were obtained via network pharmacology analyses. Network pharmacological analysis predicted the therapeutic effects of active alkaloids and several important related signaling pathways on eczema. Animal validation test showed that matrine had a significant effect on improving eczema disease. The mechanism of matrine against eczema may be related to the reduction of serum TNF-α and IL-4 levels and the down-regulation of TNF-α, STAT3 and TP53 mRNA levels.